OP0239 Phenotypic and Molecular Profile of Innate Lymphoid Cells in Chronic Synovial Inflammation. (23rd January 2014) - Hreggvidsdottir, H. S.; Mjosberg, J.; Bernink, J.; Baeten, D.; Spits, H.
Abstract : Background: Innate lymphoid cells (ILCs) represent a novel family of effector and regulatory cells in innate immunity and tissue remodelling [1 ]. The family comprises several phenotypically and functionally distinct subsets that produce various cytokines such as IL-22, IL-17, IFNγ, TNF, IL-13 and IL-5, of which many have been shown to be important in arthritis pathogenesis. Objectives: The IL-17 and IL-22 producing ILCs are of major interest as they are implicated in chronic gut inflammation [2 ]. Based on the broad clinical overlap between inflammatory bowel disease and spondyloarthritis (SpA) and the clinical importance of IL-17 in SpA we hypothesize that IL-17 and IL-22 producing ILCs contribute to inflammation and remodelling in SpA synovitis. As these cells have never been described in the joint we aimed at characterising ILCs in chronic inflammatory arthritis. Methods: ILCs (lineage negative, CD45 + CD127 + ) were analysed and sorted by flow cytometry from synovial tissue and fluid from rheumatoid arthritis (RA) and SpA patients as well as in blood from SpA patients and healthy donors. mRNA expression of sorted and expanded cells was analysed by qPCR. Results: ILCs were identified in blood as well as in synovial tissue and fluid from both RA and SpA patients. The frequency of ILCs was higher in the inflamed joint (0, 5-3, 3% of the lymphocyte population) than in the peripheral blood compartment (0, 1%). In blood, there was no marked difference in the frequency of the different ILC subset between healthy controls (n=10) and SpA patients (n=5). In the inflamed joint, the ILC3 (CRTH2 - NKp44 + ckit + ) and ILC1 (CRTH2 - NKp44 - ckit - ) populations, previously shown to express IL-22 and IFNγ respectively in other tissues, were present in all samples whereas the Th2 cytokine expressing ILC2s (CRTH2+) were found in very low frequencies. Frequencies of ILC subpopulations varied considerably between patients and no differences could be detected between RA and SpA patients. qPCR analysis of expanded cells revealed that ILC1s expressed TBX21 whereas ILC3s expressed RORC . Accordingly, stimulated ILC3s expressed transcripts for both IL-23R and IL-22 but not IL-17. Conclusions: ILC1s and ILC3s are present in the chronically inflamed joint and express the key transcription factors associated with specific cytokine profiles. These data indicate that ILCs could contribute to local cytokine-driven immune alterations in SpA and RA. References: Spits H, Cupedo T. Innate lymphoid cells: emerging insights in development, lineage relationships, and function. Annu Rev Immunol. 2012;30:647-75. Geremia, A., Arancibia-Carcamo, C. V., Fleming, M. P., Rust, N., Singh, B., Mortensen, N. J., Travis, S. P. & Powrie, F. IL-23-responsive innate lymphoid cells are increased in inflammatory bowel disease. J Exp Med 2011;208:1127-1133. Disclosure of Interest: H. Hreggvidsdottir: None Declared, J. Mjosberg: None Declared, J. Bernink: None Declared, D. Baeten: None Declared, H. Spits Employee of: AIMM Therapeutics